1994
DOI: 10.1161/01.str.25.4.814
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum cholesterol is a risk factor for both coronary heart disease and thromboembolic stroke in Hawaiian Japanese men. Implications of shared risk.

Abstract: Background and PurposeThe relation between total serum cholesterol level and thromboembolic or nonhemorrhagic stroke is controversial. The Honolulu Heart Program cohort of Japanese-American men provides data which show that elevated serum cholesterol is an independent predictor of thromboembolic stroke as well as coronary heart disease (CHD). The data are presented to suggest that the association of elevated cholesterol with stroke is sometimes underestimated or underreported partly because of competing or sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
5

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 38 publications
6
92
1
5
Order By: Relevance
“…10 The fact that the incidence of hemorrhagic stroke is higher in Asian populations has led to the hypothesis that low cholesterol, in addition to lean body weight, may be associated with increased risk of hemorrhagic strokes. 20,35 The low numbers of hemorrhagic strokes in most of the studies may explain in part the uncertainty with regard to the association between BMI and hemorrhagic stroke. Future studies are needed to determine whether lean BMI and/or low cholesterol or other factors are important contributors to hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…10 The fact that the incidence of hemorrhagic stroke is higher in Asian populations has led to the hypothesis that low cholesterol, in addition to lean body weight, may be associated with increased risk of hemorrhagic strokes. 20,35 The low numbers of hemorrhagic strokes in most of the studies may explain in part the uncertainty with regard to the association between BMI and hemorrhagic stroke. Future studies are needed to determine whether lean BMI and/or low cholesterol or other factors are important contributors to hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, however, a relatively strong and positive relationship between serum cholesterol and cerebral infarction is usually observed (25,26). Possible differences in the effects of serum cholesterol at different vascular sites could lead to the complex association between serum cholesterol levels and cerebral infarction as a single entity.…”
Section: Serum Cholesterol and Cerebral Infarctionmentioning
confidence: 99%
“…Studies of cholesterol levels in stroke patients have revealed results varying from insignificant changes to a moderate elevation [14]. There are several studies which have not found any association between lipid profile and incident ischemic stroke [15,16].…”
Section: Introductionmentioning
confidence: 99%